Superluminous Devices Versus Low-Level Laser for Temporomandibular Disorders - Sveshtarov Vasil (Sciendo, 2018)
The aim of this study is to compare the pain intensity reduction between the mean radiation doses per session of gallium-aluminum-arsenide (GaAIAs) laser with superluminous diodes (SLD) in four of the most common pain-related chronic temporomandibular disorders (TMD) - local myalgia, myofascial pain, myofascial pain with a referral, and arthralgia. This study was implemented on 124 patients with pain-related temporomandibular disorders according to the DC/TMD criteria. We applied trigger point oriented near-infrared laser (785 nm, 100 s, 8 J/cm2) and SLD cluster sessions (the cluster is composed of 49 SLDs with a combination of visible red (633 nm) and infrared (880 nm) diodes, 200 mW, 300 s, 8 J/cm2) for the temporomandibular joints and the affected muscles. Patients were evaluated at the start of the treatment, and after the 6th session of combined phototherapy. The pain intensity scores were measured according to the Visual Analogue Scale (VAS). Our results show that the most statistically manifested pain reduction is found for the SLD dose, р = 0,000118, followed by the overall dose (laser plus SLD); р = 0,001031, and the laser dose; р = 0,030942 (ANOVA dispersion analyses). Consequently, it can be concluded that myalgia is better treated through lower doses of red light compared to infrared laser doses because SLDs combine the prooxidative effect of photons with 633 nm wavelength, a large area of exposure, sufficient tissue penetration, and some positive warming thermal impact of the SLD clusters.